2005
DOI: 10.1002/rcm.1786
|View full text |Cite
|
Sign up to set email alerts
|

Determination of lincomycin and tylosin residues in honey by liquid chromatography/tandem mass spectrometry

Abstract: A simple and rapid analytical method was developed for the determination of lincomycin and tylosin residues in honey as part of field studies examining the efficacy and target animal safety of these antibiotics to control American foulbrood disease in honey bees. Residues of the antibiotics were determined using liquid chromatography/electrospray ionization tandem mass spectrometry (LC/ESI-MS/MS). Honey samples were diluted and injected directly into the LC/MS/MS system without additional cleanup by solid-phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…Um solvente mais apolar (acetato de etila) foi adicionado ao final do gradiente para remover da coluna resíduos de mel que não seriam eluídos com acetonitrila. 36,37 Em outro caso, macrolídeos e outros antimicrobianos, num total de 19 substâncias, foram extraídos de músculo e fígado de suínos, bovinos e equinos com metanol a 70%, com posterior diluição em cinco vezes com água e injeção no sistema LC-MS. Este método foi adequado para monitorar os antimicrobianos nestas matrizes e conseguiu detectar macrolídeos com relação sinal/ ruído maior que 8 em concentrações de 50 a 1000 mg kg -1 . 30 Um terceiro exemplo envolve a análise de eritromicina em trutas, onde 1 g de amostra foi misturada com água (1 mL) e o analito foi extraído a partir da adição de 4 mL de acetonitrila, agitação, sonicação e centrifugação a 10000 g. O sobrenadante foi coletado e o pelete (precipitado) foi ressuspendido em 5 mL de acetonitrila e agitado, sonicado e centrifugado novamente e o sobrenadante coletado.…”
Section: Figura 3 Estruturas Moleculares Da Tilosina a E Seus Composunclassified
“…Um solvente mais apolar (acetato de etila) foi adicionado ao final do gradiente para remover da coluna resíduos de mel que não seriam eluídos com acetonitrila. 36,37 Em outro caso, macrolídeos e outros antimicrobianos, num total de 19 substâncias, foram extraídos de músculo e fígado de suínos, bovinos e equinos com metanol a 70%, com posterior diluição em cinco vezes com água e injeção no sistema LC-MS. Este método foi adequado para monitorar os antimicrobianos nestas matrizes e conseguiu detectar macrolídeos com relação sinal/ ruído maior que 8 em concentrações de 50 a 1000 mg kg -1 . 30 Um terceiro exemplo envolve a análise de eritromicina em trutas, onde 1 g de amostra foi misturada com água (1 mL) e o analito foi extraído a partir da adição de 4 mL de acetonitrila, agitação, sonicação e centrifugação a 10000 g. O sobrenadante foi coletado e o pelete (precipitado) foi ressuspendido em 5 mL de acetonitrila e agitado, sonicado e centrifugado novamente e o sobrenadante coletado.…”
Section: Figura 3 Estruturas Moleculares Da Tilosina a E Seus Composunclassified
“…Thompson et al investigated the fate of tylosin residues in the honey from treated bees [294]. This study showed that tylosin A degrades to yield the antimicrobially active degradation product tylosin B, also known as desmycosin.…”
Section: Macrolides and Lincosamidesmentioning
confidence: 99%
“…To solve this problem, different mobile phases, suggested in the bibliography for the analysis of TA and other macrolides, were tested. There are mainly ternary mobile phases consisting of mixtures of ACN-formic acid-water [10]; methanol-01% v/v TFA in ACN or 0.1% v/v TFA in water [22]; methanol-ACN-oxalic acid [24]; ACN-heptafluorobutiric acid-ethyl acetate [23]; water-potassium phosphate buffer-THF [26]. Also, some binary mobile phases have been proposed [21,27].…”
Section: Lc Conditions 321 Mobile-phase Compositionmentioning
confidence: 99%
“…To suppress these interferences, a washing step was necessary. Taking into account different modes to solve this problem [10,22,24], some water-methanol mixtures (with 20, 40, 60, 80 and 100% of methanol) were assayed on fortified honey. The interferences were eliminated with F40% of methanol.…”
Section: Extractionmentioning
confidence: 99%
See 1 more Smart Citation